François Hotman : a revolutionary's ordeal - Kelley, Donald R., 1931- (Princeton legacy library., 1973)
The lifetime of Francois Hotman (1524-1590) was one of the most tumultuous periods in European history. Donald R. Kelley shows how this protégé of Calvin and agent of many of the great Protestant princes became involved in ecclesiastical politics, Huguenot diplomacy, and conspiracy.One of the first modern revolutionaries, Hotman rebelled not only against his family and its faith, but against the laws and eventually the government of his country. As an embittered exile lie produced a voluminous body of propaganda aimed at recovering a lost political and religious innocence on which to found a new community. At the same time he was one of the greatest and most versatile scholars of his age, achieving distinction as a jurist, teacher, classical scholar, dialectician, theologian, and historian. His Franco-Giallia and Anti-Tribonian have fascinated generations of political theorists, and his letters, reports, and anonymous works are of inestimable value to historians.Originally published in 1973.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.